Using Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (F-AHP) Methods in Criteria and Alternative Perspectives for Ranking - Qhairani Frilla F. Safiesza; Laras Mayangda Sari; M. Yogi; Alvin Andiran Sunarya; Muhammad Naufal Farras; Muhammad Fikri Evizal (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
The application of Analytic Hierarchy Process (AHP) and Fuzzy - Analytic Hierarchy Process (F-AHP) is used as the main method in conducting the ranking process in the case of choosing a major in the Department of Information System UIN Suska Riau. The perspectives of both methods are applied in two levels of hierarchy, namely on criteria and alternatives. In this experiment, AHP was used to rank the criteria, while F-AHP was used for the alternatives. The results of the experiment show that both have a CR value smaller than 0.1. The rankings obtained in order on the criteria side are RP, PD, MMK, Kindergarten and MAP. On the alternative side, the CRM course is followed by SCM, SIC, DS, ITQ, and ITG. This assessment is based on the calculation of the pairwise comparison matrix of some of the best objects from 10 experiments conducted. The conclusion that can be given is that both methods can be implemented in the case study being worked on and all have a good consistency ratio.